Termistor nanoestruturado como elemento sensor para sistema de monitoramento ambiental - FERREIRA, Marcio Kennedy Araujo (2022)
The incidence of large uncontrolled fires has increased on every continent, regardless of firefighting capabilities or strategies. One of the main tools used for fire identification and mapping is remote sensing, given the ease of construction and use, in addition to the wide operating range, however the thermistors usually used have a high cost to manufacture. In this sense, the present work aims to develop a low-cost nanostructured thermistor sensor (E-tatu) for integration into a ground forest fire monitoring system. The developed sensor consists of NTCPM synthesized by the CVD method and functionalized with COOH, the process of manufacturing macroscopic porous sheets composed of carbon nanotube networks called Buckypaper was carried out through the suspension, where 100 mg of NTCPM functionalized with COOH ( NTCPM-COOH) and then solubilized in 100 ml of hydrogen peroxide in two 200 ml beakers by means of an ultrasound bath in a Soniclean 2PS ultrasonic washer at 40 kHz for 60 minutes, then the solutions were deposited on a qualitative filter paper 37, and this filter was in a Buchner funnel that was placed in a 500 ml kitasate that was connected to a vacuum pump, as a result, a film of uniform appearance and soon afterwards it was taken to the oven (with temperature of 100° C) for complete drying of the solvent. The Buckypaper produced is 800 mm long, 100 mm wide, 205 µm thick, the copper electrodes were fixed with Mechanic Silver Conductive Ink MCN DJ002, the resistance of this Buckypaper is approximately 55.7 Ω. During tests with alternating temperature, an increase in voltage across the device was observed as the temperature increased near the flame source and under the buckypaper. This behavior can be explained by the ability of CNTs to absorb and retain heat, causing the buckypaper electrodes to heat up more than the copper electrodes, thus creating a temperature gradient between them. The results obtained suggested that carbon nanostructured devices are effective, have a quick response and are a technically and financially viable alternative to the sensors on the market. In short, the research achieved the proposed objectives, because from this study it was possible to develop an environmental monitoring system based on a nanostructured thermistor sensor. It is noticed that the use of monitoring systems for research of fires and burned areas becomes of great importance for the Amazon Region, as well as for the country as a whole.